KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN MUTU PELAYANAN KESEHATAN SANTRI DI PONDOK PESANTREN AL-JAUHAREN DI KECAMATAN PELAYANGAN KOTA JAMBI - Subhi; Musli; Ahmad Fikri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of transformational leadership in improving the quality of students’ health services at Al-Jauharen Islamic Boarding School in Pelayangan District, Jambi City. The problem addressed in this research is the limited quality of health services for students, which is influenced by constraints such as inadequate facilities, limited medical personnel, and suboptimal sanitation conditions. The objective of this study is to analyze how transformational leadership contributes to enhancing health service quality, identify supporting and inhibiting factors, and explore the efforts undertaken by the boarding school leadership. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation involving key informants such as the head of the boarding school, administrators, students, and related stakeholders. The findings reveal that transformational leadership is reflected through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This leadership approach has successfully improved the quality of students’ health services through integrated health programs, the empowerment of student health cadres (Santri Husada), the promotion of clean and healthy living behaviors, and collaboration with external institutions such as community health centers and the local health office. However, challenges remain, including limited infrastructure and the absence of permanent medical staff. Overall, transformational leadership plays a significant role in creating a healthy, religious, and sustainable boarding school environment.